Pengelolaan Bank Sampah Berbasis Teori Social Entrepreneurship: Studi pada Bank Sampah Unit Cermat Desa Suwawal Timur Kec. Pakis Aji Kab. Jepara - Dewi Srijayanti; Mamik Indaryani; Dwi Soegiarto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the management of the Cermat Waste Bank Unit in Suwawal Timur Village, Pakis Aji District, Jepara Regency, using the social entrepreneurship theory proposed by Dees (1998). The research is motivated by the limited sustainability of waste banks in Jepara, indicated by the high number of inactive units due to weak management capacity, limited innovation, resource constraints, and lack of managerial regeneration. This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, observation, and documentation. The analysis involved data reduction, data display, conclusion drawing, and was strengthened by SWOT analysis to formulate strategic recommendations. The findings reveal that social entrepreneurship practices within the Cermat Waste Bank are reflected in its strong social mission, continuous program innovation, courage in facing resource limitations, and orientation toward both social and economic value creation. Internal factors influencing sustainability include leadership, managerial commitment, and management systems, while external factors involve government support, community participation, and recycling market conditions. Recommended strategies include strengthening managerial capacity, digitalizing administrative systems, enhancing partnership networks, and diversifying circular economy-based programs. This study contributes theoretically to the development of community-based social entrepreneurship literature and practically to strengthening sustainable waste bank institutions.